Exploratory and Confirmatory Factor Analyses of Entrepreneurial Intention for Bidikmisi scholarship Students in Jambi University - Firman,; Pratama, Robin; Tersta, Friscilla Wulan (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the validity and reliability of the instrument to determine Factors Affecting Entrepreneurial Intention Among Jambi University students, the recipients of Bidikmisi Scholarship. A total of 250 students participated, selected using cluster random sampling. Survey design was used to investigate the structure of Entrepreneurial Intention factors. Quantitative data were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) using SPSS 23 and AMOS 23. EFA revealed a similar structure from previous studies and this study. The CFA approach verified the questionnaire concerning Factors Affecting Entrepreneurial Intention was satisfying for the context of students at Jambi University. This work concludes that factors Affecting Entrepreneurial Intention of Indonesian students has a four-factor structure. These findings imply the greater importance of validating and confirming the structure of students’ Entrepreneurial Intention relative to translating a construct into a different language.